Recent advances in IAP-based PROTACs (SNIPERs) as potential therapeutic agents - Chao Wang; Yujing Zhang; Lingyu Shi; Shanbo Yang; Jing Chang; Yingjie Zhong; Qian Li; Dongming Xing (Taylor & Francis Group, 2022)
Proteolytic targeting chimaeras (PROTACs) have been developed as an effective technology for targeted protein degradation. PROTACs are heterobifunctional molecules that can trigger the polyubiquitination of proteins of interest (POIs) by recruiting the ubiquitin-proteasome system, thereby inhibiting the intracellular level of POIs. To date, a variety of small-molecule PROTACs (CRBN, VHL, IAP, and MDM2-based PROTACs) have been developed. IAP-based PROTACs, also known as specific and nongenetic IAP-dependent protein erasers (SNIPERs), are used to degrade the target proteins closely related to diseases. Their structures consist of three parts, including target protein ligand, E3 ligase ligand, and the linker between them. So far, many SNIPERs have been extensively studied worldwide and have performed well in multiple diseases, especially cancer. In this review, we will present the most relevant advances in the field of SNIPERs and provide our perspective on the opportunities and challenges for SNIPERs to become therapeutic agents.